Morphologic and genetic variability in the Barbus fishes (Teleostei, Cyprinidae) of Central Italy. (6th March 2019) - Zaccara, Serena; Quadroni, Silvia; Vanetti, Isabella; Carosi, Antonella; La Porta, Gianandrea; Crosa, Giuseppe; Britton, Robert; Lorenzoni, Massimo
Abstract: Italian freshwaters are highly biodiverse, with species present including the native fishes Barbus plebejus and Barbus tyberinus that are threatened by habitat alteration, fish stocking and invasive fishes, especially European barbel Barbus barbus . In central Italy, native fluvio‐lacustrine barbels are mainly allopatric and so provide an excellent natural system to evaluate the permeability of the Apennine Mountains. Here, the morphologic and genetic distinctiveness was determined for 611 Barbus fishes collected along the Padany–Venetian (Adriatic basins; PV) and Tuscany–Latium (Tyrrhenian basins; TL) districts. Analyses of morphological traits and mitochondrial DNA sequence data explored the natural and anthropogenic factors that have shaped their distribution ranges. Over 100 alien B. barbus were recorded in the Tiber basin (TL district) and Metauro basin (PV district). Comparisons of genetic and morphometric data revealed that morphometric data could identify alien B. barbus from native Barbus, but could not differentiate between B. tyberinus and B. plebejus . Genetic analyses revealed ~50 D‐loop mtDNA haplotypes and identified a distinct Barbus lineage present only in the Vomano River at the southern boundary of PV district. Demographic expansion and molecular variance analyses revealed a lack of geographic structuring across the sampling regions. While the contemporary B. plebejus distribution has been driven primarily by anthropogenic fish translocations, the dispersal of B. tyberinus has been via natural dispersion, including their crossing of the Apennine Mountains via temporary river connectivity. The results also revealed that the Barbus fishes of the mid‐Adriatic region of Europe have a complex pattern of local endemism. To conserve these patterns of genetic uniqueness, especially in the mid‐Adriatic basins, Barbus fishes should be managed by treating them as unique evolutionary units and ceasing translocations of all Barbus fishes between river basins.